Oncological results of full thoracoscopic major pulmonary resections for clinical Stage I non-small-cell lung cancer. (24th July 2018) - Lutz, Jon A; Seguin-Givelet, Agathe; Grigoroiu, Madalina; Brian, Emmanuel; Girard, Philippe; Gossot, Dominique
Abstract: OBJECTIVES: The full thoracoscopic approach to major pulmonary resections is considered challenging and controversial as it might compromise oncological outcomes. The aim of this work was to analyse the results of a full thoracoscopic technique in terms of nodal upstaging and survival in patients with non-small-cell lung carcinoma (NSCLC). METHODS: All patients who underwent a full thoracoscopic major pulmonary resection for NSCLC between 2007 and August 2016 were analysed from an 'intent-to-treat' prospective database. Overall survival and disease-free survival were estimated using the Kaplan–Meier curves and comparisons in survival using the log-rank test. RESULTS: A total of 648 patients met the inclusion criteria, of whom 621 patients had clinical Stage I and 27 had higher stages (16 oligometastatic patients were excluded from the analysis, 11 cT3 or cT4). The mean follow-up was 34.5 months. There were 40 conversions to thoracotomy (6.3%). Thirty-day or in-hospital mortality was 0.95%. Complications occurred in 29.3% of patients. On pathological examination, 22.5% of clinical Stage I patients were upstaged. Nodal upstaging to N1 or N2 was observed in 15.8% of clinical Stage I patients. Five-year overall survival of the whole cohort was 75% and was significantly different between clinical Stages IA (76%) and IB (70.9%). For tumours <2 cm, no significant difference in overall survival was found for the segmentectomy group compared to the lobectomy group: 74% versus 78.9% ( P  = 0.634). CONCLUSIONS: Long-term survival is not compromised by a full thoracoscopic approach. Our results compared favourably with those of video-assisted techniques.